THE IMPACT OF CLASSROOM DESIGN ON STUDENT LEARNING - Daminov Zayniddin Sirojiddin o'g'li (The latest pedagogical and psychological innovations in education, 2025)
This article explores the critical relationship between classroom design and student learning outcomes. As educational spaces evolve, attention to the physical environment—including lighting, seating arrangements, color schemes, acoustics, and flexibility—has become essential in promoting student engagement and achievement. Drawing on current research and case studies, the paper highlights how a well-designed classroom can enhance concentration, support collaboration, and accommodate diverse learning styles. The findings emphasize that thoughtful architectural and interior decisions directly contribute to the academic success and emotional well-being of students. Therefore, classroom design must be considered a fundamental aspect of effective and inclusive education.